Une extrême droite du 19e siècle ? Quand la contre-révolution mobilisait en Europe - Alexandre Dupont (Cahiers d’histoire)
This article analyses the counter-revolution in nineteenth-century Europe and considers, on the basis of existing historiography, whether it is possible and relevant to present it as the extreme right of the nineteenth century. The paper first addresses conceptual problems, then examines the ideological, militant and sociological characteristics of the counter-revolution, and finally looks at the historical development of this political culture and its legacies in the 20th century. The thesis defended is that if the counter-revolution can rightly be seen as a political culture representing the extreme right in nineteenth-century Europe, the approach of comparative history and cross-history makes it possible to move away from a very Franco-centric vision which makes it the ancestor of nationalism at the end of the century. This decentring of the focus gives us a more nuanced view of the counter-revolutionary phenomenon, which presents a diversity and complexity that the term extreme right tends to obscure.